Implementation of Gender Equality and Culture of Stigma Against Women in the Employment Sector - Marito, Dwi Sihol (Semarang State University Undergraduate Law and Society Review, 2023)
The implementation of gender equality in the employment sector remains a significant challenge globally, often hindered by deep-rooted cultural stigma against women. Despite progress in legal frameworks and international conventions advocating for gender equality, women continue to face systemic barriers in accessing equal employment opportunities, fair wages, and career advancement. This paper explores the persistent cultural stigma against women in the workplace and how it undermines efforts to achieve true gender equality. The study examines various forms of discrimination, including biased hiring practices, wage gaps, limited access to leadership roles, and the undervaluation of traditionally "female" occupations. It also delves into the societal and cultural factors that perpetuate gender-based stereotypes, such as the expectation of women’s primary responsibility for household and caregiving duties, which further restrict their professional opportunities. The paper further analyzes the impact of such stigma on women’s mental and emotional well-being, highlighting the long-term effects of discrimination on women’s professional development and self-esteem. It argues that for gender equality to be fully realized in the employment sector, there needs to be a transformative shift in cultural attitudes and workplace norms, alongside the enforcement of stronger policies and regulations. The paper concludes with recommendations for organizations and governments to foster a culture of inclusivity, promote gender-sensitive policies, and address cultural stigma through education and awareness programs, thus enabling women to thrive professionally without fear of discrimination.